2011
DOI: 10.1080/09540121.2010.532536
|View full text |Cite
|
Sign up to set email alerts
|

“I feel like I'm carrying a weapon.” Information and motivations related to sexual risk among girls with perinatally acquired HIV

Abstract: Some adolescent girls perinatally infected with HIV (PIH) engage in sexual behavior that poses risks to their own well-being and that of sexual partners. Interventions to promote condom use among girls PIH may be most effective if provided prior to first sexual intercourse. With in-depth interviews, we explored gender-and HIV-specific informational and motivational factors that might be important for sexual risk reduction interventions designed to reach U.S. girls PIH before they first engage in sexual interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Adolescents, like adults, want to be loved and accepted, but due to their limited cognitive and behavioral skills, these desires may place them at risk for unfortunate consquences. 22 However, young women's sexual development differs from young men as young women struggle with traditional gender norms, power imbalances, and dynamics that can place them in risky situations. [22][23][24][25] As Marhefka and colleagues found, fear of stigma, rejection, and love among young women living with HIV, coupled with their limited sexual negation skills and the sexual power imbalances in their relationships, can provide a perfect scenario for unprotected sex and HIV transmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adolescents, like adults, want to be loved and accepted, but due to their limited cognitive and behavioral skills, these desires may place them at risk for unfortunate consquences. 22 However, young women's sexual development differs from young men as young women struggle with traditional gender norms, power imbalances, and dynamics that can place them in risky situations. [22][23][24][25] As Marhefka and colleagues found, fear of stigma, rejection, and love among young women living with HIV, coupled with their limited sexual negation skills and the sexual power imbalances in their relationships, can provide a perfect scenario for unprotected sex and HIV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, young women's sexual development differs from young men as young women struggle with traditional gender norms, power imbalances, and dynamics that can place them in risky situations. [22][23][24][25] As Marhefka and colleagues found, fear of stigma, rejection, and love among young women living with HIV, coupled with their limited sexual negation skills and the sexual power imbalances in their relationships, can provide a perfect scenario for unprotected sex and HIV transmission. 22 Therefore, secondary prevention interventions must not only increase HIV transmission knowledge but address the specific emotional and psychological barriers young women face.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Public health and prevention efforts regarding HIV need to include the general population. Several research studies have found that the pHIV-I population is very much aware of the transmissibility of infection and that the use of condom is an effective way to prevent HIV infection Fernet et al, 2007;Marhefka et al, 2011). If the general public were to attain the same sense of responsibility to themselves and to others that pHIV-I youth have achieved, HIV transmission could be lowered.…”
Section: Hiv-diagnosis This Finding Could Be Related To the Upr Pedimentioning
confidence: 99%